The Impact of the COVID-19 Pandemic on the Mental Health of Older Adults with an Intellectual Disability in Ireland. - Flannery, Fidelma (Trinity College Dublin. School of Nursing & Midwifery. Discipline of Nursing, 2024)
Background On the 11th of March 2020, the World Health Organisation declared COVID-19 a global pandemic. Governments around the world took unprecedented actions to implement public health measures to control the spread of the virus and to protect the physical health of their populations. However, it is known from previous pandemics, such as Severe Acute Respiratory Syndrome (SARS) and Middle Eastern Respiratory Syndrome (MERS) that there are implications for mental health due to restrictions such as isolating and physical distancing. The impact of such measures for individuals with an intellectual disability have not previously been reported. The prevalence of mental health conditions among this population is greater than those without an intellectual disability. Using the Hobfoll¿s Conservation of Resources Theory as a framework, this study aims to understand the role that personal and social resources had on mental health outcomes during the first eighteen months of the COVID-19 pandemic. Aim and Objectives The primary research aim in this study was to understand the personal and social resources associated with mental health outcomes for older adults with an intellectual disability in the context of the COVID-19 pandemic. The secondary aim of the study was to provide evidence to inform policy makers and service planners on the promotion of mental health in the aftermath of COVID-19, and in the event of further pandemics or public health emergencies. Within this there were three research objectives. They were to identify factors associated with mental health outcomes for this population during the COVID-19 associated restrictions; to measure how resources lost during the pandemic impacted on mental health; and to measure how resources gained during the pandemic impacted on mental health. Methods Cross sectional quantitative data was analysed from a specifically developed COVID-19 survey embedded in Wave 4 of the Irish Longitudinal Study on Ageing (IDS-TILDA), which involved a representative sample of 682 people with an intellectual disability aged 40 years and over in the Republic of Ireland. Univariate, bivariate, and multivariate analysis was carried out using binary logistic regression models across four separate studies. The impacts of gains and losses of resources on symptoms of depression, symptoms of anxiety, loneliness, and self-rated mental health were explored. Results Symptoms of depression were present in 13.6% of participants. Access to mental health supports, loss of physical health resources, and gains in resources associated with resilience were positively associated with having symptoms of depression. There were greater odds of people with Down syndrome to have symptoms of depression. Symptoms of anxiety were present among 21.5% of participants, with access to mental health supports being negatively associated with symptoms. In the regression model, resource gains associated with resilience were positively associated with having anxiety symptoms. The impact of loneliness was explored among self-reporting participants and 60% reported feeling lonely during the pandemic. Experiencing COVID-19 related stress/anxiety and loss of physical health resources were associated with being lonely. Females had greater odds of feeling lonely than men. Participants who had diagnosed mental health disorders reported poorer self-rated mental health. Losses related to physical health were also associated with poorer ratings of mental health. Within the study 182/674 participants rated their mental health as fair or poor. Conclusions There were negative impacts to mental health among older adults with an intellectual disability in Ireland during the COVID-19 associated restrictions. Using the Conservation of Resources theory to examine how losses and gains in resources impacted on mental health provided a beneficial framework for this study. Those with Down syndrome and women experienced greater mental health impacts. The importance of access to appropriate individualised mental health supports, and the impact of losses related to physical health among participants during the pandemic was highlighted. Despite the negative impacts to mental health, many participants identified positive aspects of the pandemic, suggesting coping and resilience among older adults with intellectual disabilities.
APPROVED
Keywords: COVID-19; Mental health; Older adults; IDS-TILDA; Intellectual disability